Pass the legacy : 7 keys for grandparents making a difference : awakening a retired generation to reach a wandering generation so together we can lead the youngest generation to know, love, and serve the Lord Jesus Christ /: 7 keys for grandparents making a difference : awakening a retired generation to reach a wandering generation so together we can lead the youngest generation to know, love, and serve the Lord Jesus Christ. (2018) - Jacobs, Catherine H
No abstract available